Peningkatan Agama dan Moral Melalui Demonstrasi Praktek Sholat pada Kelompok B di Raudhatul Athfal Nurul Ikhwan Kualuh Leidong Labura - Eka Lestari; Anggiat Tambunan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2019)
In this research, the developmental aspect is the development of religious and moral values. Based on the results of observations, it shows that the children of group B in RA Nurul Ikhwan have not been able to perform prayer movements. The problem in this research is how to implement, inhibit and support factors in improving religion and morals through demonstrations of prayer practices in group B in Raudhatul Athfal Nurul Ikhwan Kualuh Leidong Labura. This research method is classroom action research. This research is carried out in 2 research cycles, namely: planning, implementing, observing and reflecting in cycles 1 and 2. The data collection techniques used in the study were observation, performance, documentation and interviews. Data Collection Tool with Observation Rubric; List of performance appraisals; Documentation; Interviews and Data Analysis Techniques in this study used qualitative data analysis techniques. This research yielded significant results, namely increasing the activeness and ability to practice prayer of group B students at RA Nurul Ikhwan Kualuh Leidong, North Labuhanbatu. Based on the Developmental Achievement Level Standard (STPP) of students, it can be concluded that the average increase in students' prayer practice skills is in the pre-cycle by 11%, then in cycle 1 the average is 50%, then in cycle 2 there is an increase by an average of 90%. Keywords: Religious and Moral Values, Demonstration of Prayer Practice